Islamic Education Values in the Implementation of ‘Gernasbaku’ in Muslim Families - Anisa Dwi Makrufi; Astriani Astriani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The low literacy rate in Indonesia has attracted the attention of social elements, from the roots to the top of the leadership. The government is trying to improve literacy by launching the Gernas Baku program (National Movement for Parents to Read Books) to get children to like reading from an early age. This study aims to identify the value of education in the Gernas Baku program implemented by Muslim families of female lecturers at the Faculty of Islamic Studies, UMY. This study uses a qualitative approach with data collection techniques through interviews and documentation. The results showed that: 1) Gernas Baku program aims to support the initiative and active role of families in growing children's interest in reading through habituation at home; 2) Successful reading habits are supported by facilities provided by the family such as a reading corner or library at home, and children are invited to various places related to literacy; 3) Achievements from early childhood female lecturers of FAI UMY aged 2-4 years who have the characteristics of being honest, caring socially, being curious, appreciating achievements and liking to read; 4) Supporting factors for the Gernas Baku program are the cooperation of both parents, the interest and awareness of parents in reading assistance so that children can read and review the contents of the books they read. While the inhibiting factor is the lack of consistency of parents in providing assistance.